Evidence of Sediment Sterility and Benthic Quality as Deleterious Consequences after the 2019 oil Spill in Northeastern Brazil (Global Journal of Science Frontier Research, 2022)
The worst environmental oil spill disaster ever recorded in any tropical coastal region globally happened in 2019 severely affecting one of Brazil most famous northeast tourist area South Pirangi Reef area in the state of Rio Grande do Norte RN The oil a complex chemical mixture of hydrocarbon including heavy metals spilled on beaches in estuaries and reefs has spread between 50 cm and 1 m deep occasionally sinking to the benthos
Keywords: environmental disaster; crude oil; foraminifera; coral reef; baren zone; river